2012
DOI: 10.1111/j.1542-2011.2011.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Importance and Level of Confidence that Midwives in the United States Attach to Using Genetics in Practice

Abstract: Genetics education programs need to be developed and made available to midwives to increase their confidence levels in using genetics in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…In seven studies (Calzone et al, , ; Calzone, Jenkins, & Culp, et al ; Coleman et al, ; Godino et al, ; Pestka et al, ; Seven et al, ) the participants were specified as registered nurses. Crane et al () used certified nurse midwives (CNM) and Godino et al () used midwives in addition to registered nurses. Sussner et al () used nurse practitioners in addition to other clinicians.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In seven studies (Calzone et al, , ; Calzone, Jenkins, & Culp, et al ; Coleman et al, ; Godino et al, ; Pestka et al, ; Seven et al, ) the participants were specified as registered nurses. Crane et al () used certified nurse midwives (CNM) and Godino et al () used midwives in addition to registered nurses. Sussner et al () used nurse practitioners in addition to other clinicians.…”
Section: Resultsmentioning
confidence: 99%
“…In seven studies (Calzone et al, , ; Calzone, Jenkins, & Culp, et al ; Godino et al, ; Pestka et al, , ; Seven et al, ), the majority of participants had a bachelor degree as the highest level of education. Coleman et al () and Crane et al () reported that most participants had a master's degree. Sussner et al (), Lillie et al (), and Godino et al () did not specifically report on educational levels in their studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 37.1% of prenatal nurses ( n = 43) wished to attend a certification program in genetics specifically for nurses. By contrast, other Turkish studies conducted among nurses working in different settings and countries reported that most nurses were willing to learn more about genetics in order to enhance their professional roles (Terzioğlu & Dinç ; Crane et al ; Godino et al ; Seven et al ). Considering the low level of desire for further education in genetics in our sample, it is necessary to create awareness among prenatal nurses in Turkey about how genetics relates to their daily practice, involving the need for knowledge of genetics during PNC.…”
Section: Discussionmentioning
confidence: 86%
“…Other studies have evaluated the genetics knowledge of midwives or both midwives and nurses (Goedert et al ; Godino et al ). To our knowledge, however, few studies have focused on the genetics‐related knowledge and clinical practices of nurses or nurse–midwives, particularly in prenatal settings (Crane et al ; Lee et al ). Although prenatal nurses were among the first groups of nurses to integrate genetics into clinical practice, recent genetic advances have significantly affected prenatal practice (Lewis ; Lee et al ).…”
Section: Introductionmentioning
confidence: 99%